Cytomegalovirus infection in pregnancy - Flávia Naddeo; Ana Maria Passos-Castilho; Celso Granato (Sociedade Brasileira de Patologia Clínica, 2015)
ABSTRACTCongenital cytomegalovirus (CMV) infection is the leading cause of infectious congenital defects and disabilities. Its transmission can occur in primary and non-primary infections; however the transmission rate is considerably higher in primary infections. The diagnosis of congenital infection is complex, and there is a discussion concerning serological evaluation during pregnancy. This article aims to review the literature concerning CMV infection, its diagnosis and epidemiology.